2018
DOI: 10.1126/scisignal.aao4910
|View full text |Cite
|
Sign up to set email alerts
|

Structural principles of tumor necrosis factor superfamily signaling

Abstract: The tumor necrosis factor (TNF) ligand and receptor superfamilies play an important role in cell proliferation, survival, and death. Stimulating or inhibiting TNF superfamily signaling pathways is expected to have therapeutic benefit for patients with various diseases, including cancer, autoimmunity, and infectious diseases. We review our current understanding of the structure and geometry of TNF superfamily ligands, receptors, and their interactions. A trimeric ligand and three receptors, each binding at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
239
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(258 citation statements)
references
References 96 publications
9
239
0
Order By: Relevance
“…Additionally, the CD137L expression on HCC‐827 cells significantly induced IFN‐γ production because this could be completely inhibited by treatment with anti‐CD137 mAb. It has been suggested that CD137 is sensitive to stimulation by CD137L, so even these low expression levels might be sufficient to trigger CD137 signaling upon interaction with CD137L. More interestingly, we found that anti‐CD137 mAb can also induce the expression of PD‐L1 in lung cancer cells and synergize with IFN‐γ.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the CD137L expression on HCC‐827 cells significantly induced IFN‐γ production because this could be completely inhibited by treatment with anti‐CD137 mAb. It has been suggested that CD137 is sensitive to stimulation by CD137L, so even these low expression levels might be sufficient to trigger CD137 signaling upon interaction with CD137L. More interestingly, we found that anti‐CD137 mAb can also induce the expression of PD‐L1 in lung cancer cells and synergize with IFN‐γ.…”
Section: Discussionmentioning
confidence: 53%
“…Caspase 8) causing apoptosis [18, 29, 30]. Conversely, when TNF-alpha activates TNF-R2, recruitment of the TNF receptor-associated factors (TRAF2) occurs, resulting in stimulation of NF-kappa B, which possesses anti-apoptotic properties [19, 31]. TNF-R1 is the high affinity receptor which is internalized upon ligation whereas TNF-R2 is shed [32].…”
Section: Tnf-alpha Receptors 1 Andmentioning
confidence: 99%
“…FAS is the sixth member of the tumor necrosis factor receptor superfamily (TNFRSF6). It is the prototypic member of the death receptor subfamily, which includes the TNFRSF‐1a, ‐6, ‐10a, ‐10b, ‐12, and ‐23 proteins . All the death receptors have an intracellular death domain (DD) comprising 60‐80 amino acid residues (DD).…”
Section: Lymphocyte Apoptosis: Extrinsic Versus Intrinsic Pathwaysmentioning
confidence: 99%
“…It is the prototypic member of the death receptor subfamily, which includes the TNFRSF-1a, -6, -10a, -10b, -12, and -23 proteins. 6 All the death receptors have an intracellular death domain (DD) comprising 60-80 amino acid residues (DD). Upon interaction with FAS-ligand (FASLG), a conformational modification leads to the recruitment of a cytoplasmic adapter (the FAS-associated protein with death domain, FADD) via homotypic interactions with the DD.…”
Section: Lympho C Y Te Ap Op Tos Is: E X Trin S I C Ver Sus Intrinmentioning
confidence: 99%